HUBUNGAN ANTARA PERENCANAAN KEUANGAN PRIBADI DAN GAYA HIDUP DENGAN KEPUTUSAN MEMBELI POLIS ASURANSI JIWA PADA NASABAH ASURANSI JIWA - , Aditya Renaldi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Life insurance is a necessary financial instrument for cover personâs financial resources from family financial risk if insurers has died. Previous studies analyzed any factors related with life insurance purchase decision, includes insurerâs economic behavior and lifestyle. In fact, in Indonesia, peopleâs awareness of life insurance policy ownership still lower than any countries, and much of insurers is not know about the benefits of life insurance policy for their live. This research was conducted to observed the relationship between personal financial planning and lifestyle with life insurance policy purchase decision in life insurance clients. The main theories used in this research is consumers decision model (Blackwell, et al., 2006), decision justification theory (Connoly & Zeelenberg, 2002), theory of planned behavior (Ajzen, 1991), personal financial planning areas (Altfest, 2004), and dimension of consumers activities, interest, and opinions (Blackwell, et al., 2006